2013
DOI: 10.1038/ki.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

The Authors Reply

Abstract: We appreciate the interest of Drs Nematbakhsh and Nasri 1 in our paper. 2 Some animal models suggest that sex hormones have an important role in the development of drug-induced nephrotoxicity. As for cisplatininduced nephrotoxicity (CIN), the novel data provided by the above-mentioned authors in rats show that CIN is sex related and therefore directly affects toxicity and the potential administration of renoprotectors. Although they found no renal dysfunction in female rats with CIN when compared with male rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…On the other hand, the influence of sex on cisplatin susceptibility in rodents is less conclusive. Some researchers reported that male Wistar rats have higher susceptibility to cisplatin nephrotoxicity than females [ 122 , 171 , 172 ], while others found no difference [ 36 , 54 , 124 , 168 ]. Interestingly, in ovariectomized Wistar rats estrogen showed no effects on cisplatin nephrotoxicity [ 173 ], while in castrated Wistar rats testosterone showed protective effects at low dose but harmful effects at high dose [ 174 ].…”
Section: Factors Modifying Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…On the other hand, the influence of sex on cisplatin susceptibility in rodents is less conclusive. Some researchers reported that male Wistar rats have higher susceptibility to cisplatin nephrotoxicity than females [ 122 , 171 , 172 ], while others found no difference [ 36 , 54 , 124 , 168 ]. Interestingly, in ovariectomized Wistar rats estrogen showed no effects on cisplatin nephrotoxicity [ 173 ], while in castrated Wistar rats testosterone showed protective effects at low dose but harmful effects at high dose [ 174 ].…”
Section: Factors Modifying Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…Cisplatin is one of the most potent antineoplastics used in the treatment of various types of cancer; however, approximately one-third of patients undergoing cisplatin treatment experience acute kidney injury, with decreased glomerular filtration rate (GFR), increased serum creatinine and blood urea nitrogen (BUN), and electrolyte imbalance [1][2][3][4]. This cisplatin-induced nephrotoxicity limits the clinical use of the drug [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This cisplatin-induced nephrotoxicity limits the clinical use of the drug [1,4,5]. A wide body of experimental evidence indicates that cilastatin, a specific inhibitor of renal dehydropeptidase-I (DHP-I), can protect proximal tubular epithelial cells from the damage caused by cisplatin, without compromising the drug's therapeutic effect on cancer cells [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%